Implementasi Sistem Mitigasi Tsunami dalam Perancangan Fasilitas Pariwisata di Daerah Pesisir untuk Meningkatkan Ketahanan Terhadap Bencana Alam - Hendra Fahruddin Siregar; Dara Wisdianti (Jurnal Teknik dan Teknologi Indonesia, 2023)
The development of coastal areas as tourist destinations has been a common practice. However, after the 2004 Asia-Pacific Tsunami, several coastal areas lost their function as tourist destinations due to being devastated by the tsunami waves. To reduce the level of destruction and the number of casualties resulting from tsunamis, the design of tsunami-prone coastal areas should be based on a tsunami mitigation system. The tsunami mitigation system varies widely depending on the conditions of the area to be designed and the tsunami hazards it may face. Some of these tsunami mitigation systems not only serve as defenses against tsunamis but also function as coastal city tourist facilities. Thus, they can assist former tsunami-affected coastal areas in revitalizing their function as tourist destinations.